К фауне мошек (Diptera, Simuliidae) Полесья Украины - Лебедева, Л.И. (Вестник зоологии, 1969)
Sixty basins were investigated in the territory of the Ukrainian Polesie (in Kiev, Zhitomir and Chernigov regions) in which 21 species of Simuliidae was investigated. The most numerous species are the following: Odagmia ornata M g., Boophthora erytho-cephala De Geer, Simulium morsitans E d w.